Division of financial responsibility among mixed-gender couples - Marcin Hitczenko (Federal Reserve Bank of Atlanta, 2021)
This paper uses individuals' self-assessments of their contribution to four household activities to study how mixed-gender couples divide household responsibility. Household responsibility dynamics are characterized according to a three-point ordinal variable, whose distribution is linked to a variety of household demographics via a proportional odds model fit using survey data from both members of 327 couples. The data reveal that household tendencies depend on household demographics, albeit differently across the four activities. For household shopping, gender is the primary determinant of dynamics, with females consistently shouldering more responsibility than males. For activities more closely linked to financial decision making, however, greater responsibility aligns more with higher income and educational standing within the household. In addition, there is evidence that gender links less with role assignments in more highly educated households, but not in younger households.
Keywords: A14; C51; D13; J16; 330; gender roles; household finance; proportional odds model; Survey of Consumer Payment Choice